Marital Adjustment, Spiritual Well-Being, and Locus of Control in Married Couples - Bedir Akpınarlı, Beyzanur (Religions, 2024)
The aim of this study is to examine the relationship between marital adjustment, spiritual well-being, and locus of control in married couples. A total of 526 married individuals living in İzmir, Turkey, 283 (53.8%) women and 243 (46.2%) men between the ages of 18 and 65, participated in the research. The married individuals were evaluated individually rather than as couples. The of control scale (LCS) developed by Dağ, the marital adjustment test (MAT) developed by Locke and Wallace and adapted into Turkish by Tutarel Kışlak, the spiritual well-being scale (SWBS) developed by Ekşi and Kardaş, and a socio-demographic information form were applied to the participants. SPSS 22.0 was used for statistical analysis of the data obtained in the study. The findings were evaluated at a 5% significance level within a 95% confidence interval (p < 0.05). The findings of the study revealed that the marital adjustment of male participants was higher than that of females, and that as spiritual well-being increased, marital adjustment also increased. A positive relationship was found between transcendence, one of the sub-dimensions of spiritual well-being, and marital adjustment and internal locus of control. Similarly, a positive correlation was identified between harmony with nature and marital adjustment and internal locus of control, while a negative relationship was found between anomie and marital adjustment and internal locus of control. Moreover, negative and significant relationships were found between marital adjustment and external locus of control determinants such as belief in luck, meaninglessness of making an effort, belief in an unjust world, and anomie, one of the sub-dimensions of spiritual well-being. Additionally, a positive relationship was found between higher education and internal locus of control, and a positive relationship between marriages conducted between the ages of 17 and 20 and an external locus of control.